2016
DOI: 10.17850/njg96-2-03
|View full text |Cite
|
Sign up to set email alerts
|

Multistage Cretaceous magmatism in the northern coastal region of Ellesmere Island and its relation to the formation of Alpha Ridge – evidence from aeromagnetic, geochemical and geochronological data

Abstract: The poorly studied Alpha-Mendeleev Ridge of the Amerasia Basin of the Arctic Ocean is covered by a large magnetic high and interpreted to be part of the Cretaceous High Arctic Large Igneous Province (HALIP). At the north coast of Ellesmere Island, in the Yelverton Bay area, this characteristic magnetic high overlaps the shelf and the coastal area. Results of aeromagnetic surveys, geological fieldwork, geochronological, geochemical and Sr-Nd isotope analysis were combined to study the tectonic history of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(56 citation statements)
references
References 66 publications
6
50
0
Order By: Relevance
“…Dockman et al (2018) concluded that only the oldest phase of volcanism associated with AMR may have involved direct interaction with a hot spot. Researchers have identified HALIP components that are a continuation of AMR-related magma emplacement into the Sverdrup Basin and Canadian archipelago (Dockman et al, 2018;Estrada et al, 2016;Saumur et al, 2016) and onto Greenland, Franz Josef Land, and Svalbard (Corfu et al, 2013;Nejbert et al, 2011;Tegner et al, 2011).…”
Section: Amrmentioning
confidence: 99%
“…Dockman et al (2018) concluded that only the oldest phase of volcanism associated with AMR may have involved direct interaction with a hot spot. Researchers have identified HALIP components that are a continuation of AMR-related magma emplacement into the Sverdrup Basin and Canadian archipelago (Dockman et al, 2018;Estrada et al, 2016;Saumur et al, 2016) and onto Greenland, Franz Josef Land, and Svalbard (Corfu et al, 2013;Nejbert et al, 2011;Tegner et al, 2011).…”
Section: Amrmentioning
confidence: 99%
“…The HPVC together with the rhyodacite has an age range of c. 104-74 Ma and includes the mildly alkaline WIC (93-92 Ma). Estrada et al (2016) further find that the northern coast of Ellesmere Island shows some characteristic features of a magma-rich rifted margin indicating an extensional evolution parallel to the North American margin between the openings of the Canada Basin and the Eurasian Basin. On the basis of their Sm-Nd isotopic results, Kingsbury et al (2016) find that South Fiord intrusion magmas were derived from a homogeneous mantle source whereas a more heterogeneous source is invoked for the Isachsen Formation lavas.…”
Section: Estrada Et Al (2016)mentioning
confidence: 68%
“…Here, a characteristic magnetic high overlapping the shelf and coastal area is interpreted to be a part of the Cretaceous High Arctic Large Igneous Province (HALIP). Estrada et al (2016) find that the basement, consisting of metamorphic rocks of the Pearya Terrane, was strongly affected by HALIP-related magmatism that is responsible for the characteristic positive magnetic anomaly patterns. They document that a broad magnetic high which can be traced to the Alpha Ridge and covers the shelf and coastal areas of Yelverton Bay, is caused by a voluminous intrusion into the continental crust at a depth of c. 6-15 km.…”
Section: Estrada Et Al (2016)mentioning
confidence: 82%
See 2 more Smart Citations